2019
DOI: 10.1007/s10826-019-01400-0
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Tuning in to Kids Parenting Program in Iran for Reducing Preschool Children’s Anxiety

Abstract: Objectives Tuning in to Kids (TIK) is a group parenting program that targets parent emotion socialization (emotional awareness and regulation, meta-emotion and emotion coaching skills) to improve children's functioning. The aim of this pilot study was to investigate the effectiveness of this program when used with parents of anxious preschool children. Methods The study used a randomized controlled design. Fifty-six mothers of children who scored one standard deviation above the mean on the parent report of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…Havighurst et al (2013) also showed that ECPP significantly reduced the extent and severity of behavioral problems, indicating that this treatment is effective for childhood disorders. A randomized controlled study by Edrissi et al (2019) demonstrated a significant difference between participants in the parenting program group and control group on parent-reported anxiety at post-test and 6-month follow-up. Our results are important because few parenting programs have shown improvement in symptoms of children's internalizing disorders.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Havighurst et al (2013) also showed that ECPP significantly reduced the extent and severity of behavioral problems, indicating that this treatment is effective for childhood disorders. A randomized controlled study by Edrissi et al (2019) demonstrated a significant difference between participants in the parenting program group and control group on parent-reported anxiety at post-test and 6-month follow-up. Our results are important because few parenting programs have shown improvement in symptoms of children's internalizing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One booster session was held one month after the initial seven sessions (Table 1). Different exercises in the program were provided to teach Gottman's five steps, with content specified as core, optional, or home activities (Edrissi et al, 2019). The program inspired modifications in parenting attitudes and behaviors while increasing the emotional contact between parents and children.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations